W139 van Warmoesstraat naar Post CS. - Demeester, Ann (Amsterdam : Roma Publications Amsterdam, 2004)
Keaton, Buster ; Potrc, Marjetica ; Marcel, Didier ; Galegati, Stefania ; Van den Bosch, Steve ; Bryssinck, Hans ; Peeters, Diederik ; Vermeersch, Pieter ; Ottaviano, Elise ; Brouwers, Joris ; Zuffi, Italo ; de Vries, Anne ; Goiris, Geert ; Koronczi, Endre ; Sailstorfer, Michael ; Niscino, Tazro ; PROTEC Documentation Services ; Xhafa, Sislej ; Kiaer, Ian ; Sissi ; Meester, Joanneke ; Taudin Chabot, Raymond ; Muhirwa, Ciza ; Audéoud, Fabienne ; Colson, Vaast ; Kruysen, André ; Meuris, Wesley ; Passens, Gregor ; Vanden Meersch, Els ; Heiremans, Ronny ; Wöhrl, Martin ; Vermeir, Katleen ; Van Imschoot, Jan ; Birza, Rob ; 't Jolle, Sven ; Savic-Gecan, Tomo ; Seric, Husman Ana ; Andreasen, Kasper ; Hunneman, Hendrik-Jan ; van Gameren, Sarah ; Luijters, Rudy J. ; Mohr, Thomas ; Berlanger, Marcel ; Cornelissen, Robbie ; Dolron, Désirée ; Graven & Rebers ; Krijl, Evelien ; Leroy, Dominique ; Margolis, Alisa ; Rostovsky, Peter ; Ruilova, Aïda ; Williams, Michelle ; Holten, Katie ; Muka, Edi ; Qëndro, Gezim ; Sala, Anri ; Groner, Sagi ; Leegte, Jan Robert ; van Gerwen, Patrick ; Paulus, Edo ; Project...euh ; Beltrán, Erick ; Berchem, Otto ; Moffatt, Tracey ; Bachzetsis, Alexandra ; Mooij, Olaf ; Kokesh, Adam ; Holzfeind, Heidrun ; Basarab, Liliana ; Bäckström, Miriam ; Calovski, Yane ; Framis, Alicia ; Jónsson, Haraldur ; Lislegaard, Ann ; Raila, Arturas ; Sjöberg, Tobias ; Soi, Praneet ; Ziura, Darius ; Floc'h, Nicolas ; Buxó, Thomas ; Stig, Martine ; Van Kerckhoven, Anne-Mie ; Pawlowski, Mauro ; Lindfors, J. ; Björgulfsson, Heimir ; Van Braak, Kevin ; Bunga, Carlos
lijst met tentoonstellingen en projecten in W139 Amsterdam van 30.11.2002 - 23.02.2003.
Nederlands
boek